Prevalence and Antibiotic Susceptibility Pattern of Multidrug-Resistant Pseudomonas aeruginosa in a Tertiary Hospital, South Sumatera, Indonesia - Ningtiyas, Salwa Adilah; Saragih, Dinda Azzahrah; Nafisah, Nusyur Azka; Nawawi, Rizki Andini; Rivani, Erizka; Diba, Masayu Farah; Zanaria, Rima (Faculty of Medicine, Universitas Diponegoro, 2026)
ABSTRACTBackground: Pseudomonas aeruginosa is a Gram-negative bacterium that causes opportunistic and healthcare-acquired infections. Its ability to rapidly acquire antibiotic resistance complicates treatment, prolongs hospitalization, and increases morbidity, mortality, and healthcare costs. Objective: This study aimed to determine the prevalence and antibiotic susceptibility pattern of multidrug-resistant P. aeruginosa at Dr. Mohammad Hoesin General Hospital, South Sumatera, Indonesia.Methods: A descriptive observational study with a cross-sectional design was conducted using data from the Clinical Microbiology Laboratory and Medical Records Installation of Dr. Mohammad Hoesin General Hospital, Palembang, from May 2022 to April 2023. Data were analyzed univariately and presented through tables, figures, and descriptive summaries.Results: A total of 465 hospitalized patients were found to be infected with P. aeruginosa. Adult patients aged 18–65 years were the most affected (71%). The leading primary diagnoses were diabetic foot ulcer, pneumonia, and sepsis. Most patients were hospitalized for 8–14 days (25.2%). Antibiotic susceptibility testing showed the highest sensitivity to amikacin (94.2%), while the lowest was observed with meropenem and ceftazidime. The resistance profile included 24.7% MDR, 6.7% XDR, 0.9% probable PDR, and 2.4% DTR isolates.Conclusion: P. aeruginosa infections were predominantly found in adult patients with prolonged hospitalization. Amikacin remains the most effective antibiotic, while cefazolin and tigecycline showed poor efficacy. The presence of MDR, XDR, PDR, and DTR strains highlights the urgent need for rational antibiotic use and strengthened antimicrobial stewardship programs. Keywords:Pseudomonas aeruginosa, Hospitalized patients, Antibiotic resistance, Multidrug resistance